Stereotypic vision how stereotypes disambiguate visual stimuli. [article]. - Correll, Joshua; Crawford, Matthew T.; Wittenbrink, Bernd
Three studies examined how participants use race to disambiguate visual stimuli. Participants performed a first-person-shooter task in which Black and White targets appeared holding wither a gun or an innocuous object (e.g., a wallet). In Study 1, diffusion analysis (Ratcliff, 1978) showed that participants rapidly acquired information about a gun when it appeared in the hands of a black target, and about an innocuous object in the hands of a white target. For counterstereotypic pairings (armed whites, unarmed blacks), participants acquired information more slowly. In Study 2, eye tracking showed that participants on more ambiguous information (measured by visual angle from fovea) when responding to stereotypic targets; for counterstereotypic targets, they achieved greater clarity before responding. In Study 3, participants were briefly exposed to targets (limiting access to visual information) but had unlimited time to respond. In spite of their slow, deliberative responses, they showed racial bias. This pattern in inconsistent which control failure and suggests that stereotypes influenced identification of the object. All 3 studies show that race affects visual processing by supplementing object information. - - (from the authors)